Pro-vitamin A carotenoid content of 48 plantain (Musa AAB genome) cultivars sourced from eastern Democratic Republic of Congo - Blomme, Guy; Ocimati, W.; Nabuuma, D.; Sivirihauma, Charles; Davey, M.; Buah, Saaka S.J.; Bergh, Inge van den; Vutseme, L.; Bahati, L.; Ekesa, B. (Wiley, 2020)
Vitamin A deficiency (VAD) is widespread in sub‐Saharan Africa (SSA). Unlike in developed countries, where the main source of vitamin A comes from meat, the diet of poor populations in SSA is largely plant based. It is thus important to identify local / popular plants with higher vitamin A content for combating VAD. Banana (including plantains) is an important staple food crop in this region. The identification and promotion of vitamin A‐rich banana cultivars could contribute significantly to the alleviation of VAD in areas heavily dependent on the crop. We assessed pro‐vitamin A carotenoid (pVACs) content in the fruit pulp of 48 local plantains from eastern Democratic Republic of Congo, to identify cultivars that could help reduce VAD, especially among young children and women of reproductive age.